Anxiety disorders in schizophrenia - the importance of differentiation and targeted treatment a case report and literature review - Grajnert, Filip; Bińczyk, Wiktoria; Dróżdż, Olgierd; Siudek, Bartosz; Plizga, Jakub; Głuszczyk, Agnieszka; Kamiński, Mateusz; Kuśmierczyk, Katarzyna; Karkos, Patrycja (Quality in Sport, 2024)
Schizophrenia is a chronic mental disorder characterized by severe cognitive and behavioral impairments. It often coexists with multiple and complex anxiety symptoms that exacerbate the clinical challenges associated with schizophrenia. This case report presents the history of a 32-year-old woman with a final diagnosis of both paranoid schizophrenia and mixed anxiety disorders. The patient presented with persistent auditory pseudohallucinations, severe anxiety together with occasional panic attacks, which were treated with a variety of antipsychotics. Treatment adjustments were necessitated by the emergence of side effects, including neutropenia, motor disturbances and the observation of major anxiety symptoms, including panic disorder. Ultimately, the successful use of quetiapine in monotherapy was achieved. This case study emphasizes the need for comprehensive treatment strategies to address the complex interplay of psychotic and anxiety symptoms. Increased clinical awareness and targeted treatment of comorbid anxiety can significantly improve the quality of life of patients with schizophrenia.